The handbook of mergers and acquisitions - Faulkner, David, 1938-; Teerikangas, Satu.; Joseph, Richard J. (Oxford : Oxford University Press, 2012)
This text bridges hitherto separate disciplines engaged in research in mergers and acquisitions to integrate strategic financial, socio-cultural, and sectoral approaches to the field. It examines the management processes involved, as well as valuations and post-acquisition performance.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Consolidation and merger of corporations